Measuring and changing control: Women's empowerment and targeted transfers - Ingvild Almås; Alex Armand; Orazio Attanasio; Pedro Carneiro (Centre for Microdata Methods and Practice (cemmap), 2015)
This paper studies how targeted cash transfers to women affect their empowerment. We use a novel identification strategy to measure women's willingness to pay to receive cash transfers instead of their partner receiving it. We apply this among women living in poor households in urban Macedonia. We match experimental data with a unique policy intervention (CCT) in Macedonia offering poor households cash transfers conditional on having their children attending secondary school. The program randomized whether the transfer was offered to household heads or mothers at municipality level, providing us with an exogenous source of variation in (offered) transfers. We show that women who were offered the transfer reveal a lower willingness to pay, and we show that this is in line with theoretical predictions.
Keywords: D13; O12; J16; 330; gender; empowerment; cash transfers; intra-household